Geometrically nonlinear bending analysis of functionally graded beam with variable thickness by a meshless method. (1st April 2018) - Lin, Jun; Li, Jiao; Guan, Yanjin; Zhao, Guoqun; Naceur, Hakim; Coutellier, Daniel
Abstract: Geometrically nonlinear bending deformation of Functionally Graded Beams (FGBs) with variable thickness is simulated by a meshless Smoothed Hydrodynamic Particle (SPH) method. The material properties of FGB is assumed to be varied smoothly in the thickness according to exponent-law distribution. To prevent the mesh-distortion in element-based numerical method, meshless SPH method is adopted, where corrective smoothed particle method and total-Lagrangian formulation are employed to improve its precision and stability. To validate the present SPH method, several numerical examples are performed and compared to analytical and finite element solutions.